Antioxidant Activity of Nipa Palm (Nypa fruticans Wurmb) Leaf Ethanol Extract: Analysis Based on DPPH Radical Scavenging and FRAP Reducing Power Assays - Permata, Bangkit Riska; Wicahyo, Septian Maulid; Raharjo, Danang (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Background: The search for natural antioxidants as alternatives to synthetic ones is crucial due to safety concerns. Nipa palm (Nypa fruticans Wurmb) leaf, an abundant mangrove waste product in Indonesia, is a potential source of natural antioxidants but remains understudied, particularly regarding its reducing power capacity. Objective: This study aimed to evaluate the antioxidant activity of nipa palm leaf ethanol extract through two mechanisms: free radical scavenging activity (DPPH method) and ferric reducing antioxidant power (FRAP method).Methods: Dried nipa leaf powder was macerated with 70% ethanol. The antioxidant activity was determined by the DPPH method to obtain the IC?? value and by the FRAP method to measure the reducing power expressed as µM Fe(II) equivalent per gram of extract. Vitamin C and Quercetin were used as standards for the DPPH and FRAP assays, respectively.Results: The extraction yield was 15%. The nipa leaf extract exhibited very strong antioxidant activity with an IC?? value of 42.08 µg/mL in the DPPH assay. Furthermore, the FRAP assay confirmed its potent reducing capacity, with a value of 2850.50 µM Fe(II)/g extract.Conclusion: The ethanol extract of nipa palm leaves demonstrates potent antioxidant activity through both free radical scavenging and reducing power mechanisms. These findings suggest that nipa leaf, currently an underutilized waste product, is a promising source of natural antioxidants for potential applications in the food, cosmetic, and pharmaceutical industries.